2018
DOI: 10.1016/j.yrtph.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of novel tobacco heating product THP1.0. Part 3: Comprehensive chemical characterisation of harmful and potentially harmful aerosol emissions

Abstract: For a tobacco heating product (THP), which heats rather than burns tobacco, the emissions of toxicants in the aerosol were compared with those in cigarette smoke under a machine-puffing regimen of puff volume 55 ml, puff duration 2 s and puff interval 30 s. The list of toxicants included those proposed by Health Canada, the World Health Organization Study Group on Tobacco Product Regulation (TobReg), the US Food and Drug Administration and possible thermal breakdown products. In comparison to the University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
178
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(189 citation statements)
references
References 20 publications
9
178
0
2
Order By: Relevance
“…Our findings concur with findings from e-cigarette studies [68] as well as from manufacturer and independent data on HTPs. Findings from tobacco industry reports indicate negligible CO emission (0,436 mg/stick and 0,223 mg/stick for iQOS and GLO, respectively; compared to 30.2 mg/tobacco cigarette, that is 69,3 and 135,4 times less) [13, 14]. Independent analytical chemistry data confirms substantial CO level reductions [15, 16] in HTP aerosol emissions compared to combustible cigarettes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings concur with findings from e-cigarette studies [68] as well as from manufacturer and independent data on HTPs. Findings from tobacco industry reports indicate negligible CO emission (0,436 mg/stick and 0,223 mg/stick for iQOS and GLO, respectively; compared to 30.2 mg/tobacco cigarette, that is 69,3 and 135,4 times less) [13, 14]. Independent analytical chemistry data confirms substantial CO level reductions [15, 16] in HTP aerosol emissions compared to combustible cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…However, surprisingly, in two of these studies, when exposure to CO was evaluated by measurement in exhaled breath, a significant elevation was detected [13, 14]. It is possible that combustion can still take place in some HTPs designs.…”
Section: Introductionmentioning
confidence: 99%
“…The tobacco industry has performed multiple studies regarding health consequences of HTP use. The results of in vitro and in vivo studies indicate that HTP aerosols have lower toxicity and no new hazards compared to conventional cigarette smoke [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The results of humanbased studies also suggest that switching from conventional cigarettes to IQOS or glo leads to reductions in exposure to smoke toxicants in a manner comparable to quitting tobacco use [74][75][76][77][78].…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 94%
“…Following the manufacturer recommendations, especially proper cleaning of the device after each 20 tobacco sticks seems to be crucial to provide proper thermal regulation and reduce emissions of harmful substances. Most of the research regarding the chemical composition of generated aerosol was carried out on brand new, never used devices [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Independent researchers showed that the use of 1 IQOS tobacco stick left a significant amount of debris, fluid, and fragments of cast-leaf in the device holder [8].…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 99%
“…This is expected to result in lower levels of toxic emissions and, as a result, they are marketed as reduced‐risk products. Several studies have assessed the chemistry and toxicology of this and other similar products from other manufacturers . However, with few exceptions , all studies have been performed by the manufacturers of the products.…”
Section: Introductionmentioning
confidence: 99%